"One Man's Meat Is Another Man's Poison": Marungi and Realities of Resilience in North West Uganda. Issue 2 (3rd July 2022) - Storer, Elizabeth; Anguyo, Innocent; Odda, Anthony
ABSTRACT: Approaches to resilience in post-war contexts prioritise systems-based thinking above everyday realities. This paper explores reconstruction through marungi (khat) in North-West Uganda. Presenting ethnographic evidence, we chart connections between marungi and resilience among growers, traders and "eaters". Firstly, we argue for a consideration of the actual resources through which individuals and households build capacity to withstand shocks following war. Secondly, we explore inequities within production lines and the effects of criminalising khat, to demonstrate trade-offs within prospects for post-war prosperity. Ultimately, we argue for process-based analyses of how resilience is negotiated in contingent circumstances.